miR-31 Links Lipid Metabolism and Cell Apoptosis in Bacteria-Challenged Apostichopus japonicus via Targeting CTRP9 - Shao, Yina; Li, Chenghua; Xu, Wei; Zhang, Pengjuan; Zhang, Weiwei; Zhao, Xuelin (Frontiers in Immunology, 2017)
The biological functions of miRNA have been studied in a number of eukaryotic species. Recent studies on vertebrate animals have demonstrated critical roles of miRNA in immune and metabolic activities. However, studies on the functions of miRNA in invertebrates are very limited. Here, we demonstrated that miR-31 from Apostichopus japonicus disrupts the balance of lipid metabolism, thus resulting in cell apoptosis by targeting complement C1q tumor necrosis factor-related protein 9 (AjCTRP9), a novel adipokine with pleiotropic functions in immunity and metabolism. Lipidomic analysis suggested that the intercellular lipid metabolites were markedly altered, and three ceramide species synchronously increased in the AjCTRP9-silenced coelomocytes. Moreover, exogenous ceramide exposure significantly induced apoptosis in the coelomocytes in vivo, in agreement with findings from miR-31 mimic- or AjCTRP9 siRNA-transfected coelomocytes. Furthermore, we found that the imbalance in sphingolipid metabolism triggered by the over-production of ceramides ultimately resulted in the activation of the apoptosis initiator caspase-8 and executioner caspase-3. Our findings provide the first direct evidence that miR-31 negatively modulates the expression of AjCTRP9 and disturbance of ceramide channels, thus leading to caspase-3- and caspase-8-dependent apoptosis, during the interactions between pathogens and host.